2016
DOI: 10.1177/1352458516682105
|View full text |Cite
|
Sign up to set email alerts
|

Breaking down the gut microbiome composition in multiple sclerosis

Abstract: Background:The gut microbiome, which consists of a highly diverse ecologic community of microorganisms, has increasingly been studied regarding its role in multiple sclerosis (MS) immunopathogenesis. This review critically examines the literature investigating the gut microbiome in MS. Methods: A comprehensive search was performed of PubMed databases and ECTRIMS meeting abstracts for literature relating to the gut microbiome in MS. Controlled studies examining the gut microbiome in patients with MS were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 46 publications
3
40
0
1
Order By: Relevance
“…There are still many questions about how gut bacteria can influence the course of immunity at organs distant from the gut, and whether same bacteria may influence immunity differentially in autoimmune conditions vs. cancer. For example, Bifidobacteria, Akkermansia, and Bacteroides are increased in patients with MS, but may lead to anti-tumor outcomes in cancer patients (195,196). Research to better delineate which bacterial species are most conducive to promoting favorable vs. unfavorable immune outcomes in MS and cancer, will help to pave the road toward more precise risk assessment and manipulation of the gut microbiome in patients with MS and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…There are still many questions about how gut bacteria can influence the course of immunity at organs distant from the gut, and whether same bacteria may influence immunity differentially in autoimmune conditions vs. cancer. For example, Bifidobacteria, Akkermansia, and Bacteroides are increased in patients with MS, but may lead to anti-tumor outcomes in cancer patients (195,196). Research to better delineate which bacterial species are most conducive to promoting favorable vs. unfavorable immune outcomes in MS and cancer, will help to pave the road toward more precise risk assessment and manipulation of the gut microbiome in patients with MS and cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Similarities in the microbial composition and functions among healthy individuals are suggestive of a core microbiome that is required for host health [25]. Many diseases, ranging from metabolic (e.g., obesity and type 2 diabetes) to autoimmune (e.g., multiple sclerosis) and neurodegenerative (e.g., Alzheimer’s disease), have now been linked to dysbiosis [26,27,28] and extensive research efforts have gone into developing treatments to achieve a healthy microbiome. Given that host diet is a key determinant of the gut microbial profile and eating disorders are characterized by dysregulated food intake, it is only logical to assume at least an associative relationship between eating disorders and an altered gut microbiota.…”
Section: Gut Microbiota: a Missing Piece In Eating Disordersmentioning
confidence: 99%
“…Psychiatric and neurodevelopmental illnesses, including major depressive disorder [49,50], autism spectrum disorder [51], and multiple sclerosis [26], are consistently associated with a state of dysbiosis. Gut microbes are required for normal brain function.…”
Section: Gut Microbiota: a Missing Piece In Eating Disordersmentioning
confidence: 99%
“…43 Although the precise pathomechanism is unclear, autoimmunity, genetic background, and environmental factors, such as infections and latitude, appear to contribute to disease onset and exacerbation. 44 Among environmental factors, the gut microbiota has also been proposed to be associated with the pathogenesis of MS. 13,45,46 In high-income countries, lifestyle westernization, including food, water, and sanitation, has decreased several infectious diseases, such as viral hepatitis, and helminth infestations, while chronic inflammatory and autoimmune diseases, including MS and IBD, have been increased. 47 Particularly, “western diet”, rich in fat and salt, has been associated with the increased incidence of MS and IBD.…”
Section: Gut Microbiota In Ms and Its Animal Modelsmentioning
confidence: 99%
“…45 Case-control studies demonstrated that the microbiome of MS patients differs from that of controls, although it is unknown whether the altered microbiota is a cause or result of development of MS (Table 3). In MS, reproducible changes of microbial taxa are limited, partly because each study often analyzed microbiome at different taxonomic ranks.…”
Section: Gut Microbiota In Ms and Its Animal Modelsmentioning
confidence: 99%